Pemanfaatan Teknologi Gadget Sebagai Media Pelajaran - Triastuti, Neni; Harahap, Cece (Jurnal Masyarakat Indonesia (Jumas), 2023)
This community service activity is in the form of an introduction to the use of gadgets as learning media. Just like other technologies, gadgets also have advantages that can be used as a support for reading and learning facilities for students. The purpose of this research is to find out whether using gadget media can create an effective learning atmosphere for students. The results showed that gadgets were used by students to make it easier to access subject matter, watch and analyze learning films or videos. With the use of gadgets, students become more interesting and learning becomes more varied and fun.